Volunteering as a phenomenon of Ukrainian consciousness (from individual to general national assistance) - Rabiichuk Serhii (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The article examines some aspects of volunteering as a phenomenon of Ukrainian consciousness (from individual to national assistance). It has been established that today this is an absolutely unique phenomenon of Ukrainian society. It was found that people created an effective voluntary system of volunteer organizations, individual volunteers, public organizations, charitable foundations, which took responsibility for solving social and military problems. The purpose of the article is to analyze the evolution of volunteerism as a phenomenon of Ukrainian consciousness from individual help to national help. The applied research methods are: analysis (interpretation of literary sources in order to identify their essence, main purpose), comparison (allows to establish common and distinctive features between objects, processes, phenomena), generalization (allows to establish common properties in processes). It has been proven that all volunteer activities are based on the principle of voluntariness – a useless socially important activity. It is substantiated that volunteerism is characteristic of democratic, highly developed societies, and for such citizens the issue of self-realization and self-improvement through socially useful work has become more important. It was established that the principle of voluntariness contributes to the realization of the volunteer’s civic position, which in turn forms social consciousness. It has been established that volunteer activity in Ukraine has its own characteristics that distinguish it from others: independence and initiative of volunteers and volunteer organizations; acquisition by volunteer activity of its place in the system of organizations exerting influence on social processes; formation of many volunteers as true, dedicated patriots; the formation of volunteer activity, as a result of the state’s inability to ensure the functioning of many directions and spheres of public life, etc.